2006
DOI: 10.1603/0046-225x-35.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone of the Soybean Aphid,Aphis glycinesMatsumura, and Its Potential Use in Semiochemical-Based Control

Abstract: The newly invasive soybean aphid, Aphis glycines Matsumura, has seriously threatened soybean production in North America, after having spread to >20 states in the United States and several southern provinces of Canada. Control of A. glycineshas focused on applications of insecticides, which are not a long-term solution to soybean aphid pest management. In autumn, soybean aphids start producing alate females (gynoparae) that search for their overwintering host plants, the common buckthorn, Rhamnus cathartica. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Rhamnus cathartica is the primary overwintering host plant for the soybean aphid, Aphanes glycines Matsumura, a newly invasive threat to soybean production in North America (Zhu et al 2006). Originally discovered in Wisconsin in 2000, this pest had already spread to three Canadian provinces and 20 US states by 2004 (Ragsdale et al 2004; see also Section 13c).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhamnus cathartica is the primary overwintering host plant for the soybean aphid, Aphanes glycines Matsumura, a newly invasive threat to soybean production in North America (Zhu et al 2006). Originally discovered in Wisconsin in 2000, this pest had already spread to three Canadian provinces and 20 US states by 2004 (Ragsdale et al 2004; see also Section 13c).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…The soybean aphid, Aphis glycines Matsumura (Hemiptera, Aphididae), first appeared in North America (Wisconsin) in 2000 (Zhu et al 2006). Rhamnus cathartica is considered to be ''the primary host species of most importance to the aphid's pest status in soybean'' (Voegtlin et al 2005).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Headspace collection (air entrainment) of oviparae of a number of aphid species indicate that the ratio of the two pheromone components emitted by oviparae is relatively species-specific (Hardie et al 1999;Boo et al 2000;Goldansaz et al 2004;Stewart-Jones et al 2007 and references therein;Dewhirst et al 2010 and references therein), and prior research indicates that while male aphids will respond to a range of ratios of the two components, they tend to exhibit a greater response to the ratio emitted by conspecific oviparae Hardie et al 1990;Lilley and Hardie 1996;Boo et al 2000). It also has been suggested that aphid sex pheromones may act as aggregation pheromones for gynoparae Powell and Hardie 2001;Zhu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory and field studies have shown the impacts of synthetic and natural sources of aphid sex pheromones on male aphid behavior and trap catches, many reporting significant responses to specific sex pheromone ratios (e.g., Pettersson 1970;Dawson et al 1988;Campbell et al 1990;Hardie et al 1990Hardie et al , 1996Guldemond et al 1993;Lilley and Hardie 1996;Thieme and Dixon 1996;Boo et al 2000;Goldansaz et al 2004;Zhu et al 2006;Dewhirst et al 2008). The respective sex pheromones for H. pruni or B. helichrysi have not previously been identified, and identification would provide a foundation for developing pheromone-based approaches for monitoring and management of these aphid pests in damson and prune crops.…”
Section: Introductionmentioning
confidence: 99%
“…Using the electroantennogram (EAG) technique, Zhu et al (2006) demonstrated that gynoparae and male soybean aphids responded to two sex pheromonesÑ(4aS,7S,7aR)-nepetalactone (Z,E-nepetalactone) and (1R,4aS,7S,7aR)-nepetalactol (Z,E-nepetalactol)Ñalone or in combination. Zhu et al (2006) also showed that pheromone receptors are present in spring and summer migrants.…”
mentioning
confidence: 99%